Selection of antimicrobial agents in the composition of elderberry extract syrup - Khokhlenkova, Natalia; Kaliuzhnaia, Olha; Dvinskykh, Nataliia (Annals of Mechnikov's Institute, 2025)
Introduction. In modern pharmacy, there is growing interest in herbal medicines, which usually have low toxicity and mild effects. Syrups with plant extracts are particularly relevant because of their high therapeutic effectiveness and ease of use. It is important to consider the microbiological stability of syrups, as they provide a favorable environment for microorganisms. The Biotechnology Department at NUPh is developing a syrup from black elderberry, which possesses antioxidant and anti-inflammatory properties. To avoid deterioration of product quality, it is crucial to investigate the optimal concentration of preservatives. The aim of the work. To conduct microbiological studies during the pharmaceutical development stage of the syrup containing black elderberry extract with adaptogenic, anti-inflammatory, and immunostimulatory effects. Materials and Methods. The objects of study were syrup samples without preservatives and those with added methylparaben, propylparaben, potassium sorbate, sodium benzoate, and their combinations. The effectiveness of antimicrobial preservatives was tested according to the methodology specified in SPhU 2.7, V. 1 (5.1.3). The studies were conducted in aseptic conditions within a laminar flow cabinet (Biosafety cabinet AS2-4E1 «Esco», Indonesia). Results. The growth properties of nutrient media and the suitability of the methodology for determining the total number of viable cells were verified. The study demonstrated the importance of including antimicrobial preservatives in the syrup to ensure compliance with established standards for microbiological stability. The effectiveness testing of the antimicrobial preservatives yielded the following results: after 14 days of storage, the antimicrobial action of the syrup with sodium benzoate was ineffective, and the results for P. aeruginosa and fungi C. albicans and A. brasiliensis did not meet SPhU requirements. Syrups with potassium sorbate at concentrations of 0.1% and 0.2% also failed to meet the criteria. The combination of methylparaben and propylparaben, as well as the combination of potassium sorbate and sodium benzoate, proved effective and met the requirements for ensuring microbiological stability. Conclusions. The tests demonstrated the necessity of adding antimicrobial preservatives to the syrup containing elderberry extract. High antimicrobial efficacy was shown by samples containing combinations of sodium benzoate and potassium sorbate, as well as methyl- and propylparabens. Considering certain factors, the first combination of preservatives was selected. Samples of syrup with the chosen preservatives were prepared for storage for further research.